Study of The Pandemic Impact of Covid-19 on Road Project Performance in South Sulawesi Province - Hasrisal Hasrisal; Muhammad Asad Abdurrahman; Muhammad Isran Ramli (Lowland Technology International, 2022)
The road is a means of circulation space which is made to facilitate transportation by land. Roads have existed since ancient human times and were used to move places and be passed to transport life's equipment, in human development only know roads made of soil that can only be passed on foot or using livestock such as horses, cows or cattle. buffalo. The impact of the spread of Covid-19 has resulted in certain conditions so that efforts to overcome them need to be carried out, one of which is through large-scale social restrictions (PSBB). Based on these considerations, President Joko Widodo has issued Government Regulation (PP) Number 21 of 2020 concerning Large-Scale Social Restrictions in the Context of Accelerating the handling of Covid-19 which was signed on March 31, 2020. Covid-19 pandemic, the performance was measured from the time during the COVID-19 pandemic and after the Covid-19 pandemic with worker productivity and the distance between workers in the field, the level of productivity in projects during the Covid-19 pandemic was 1,284 m3, the distance between workers was 0.894 m, project performance as measured by cost performance during the covid-19 pandemic and after the Covid-19 pandemic - 19 with the BCWSN method until week 11 the realization of the work was 45.72% the cost was Rp. 34,606,561.52. Projects after the Covid-19 pandemic realized 58.61% of work at a cost of Rp. 43,100,392,05, Project performance as measured by work safety performance during the COVID-19 pandemic and the post-Covid-19 pandemic, distributing questionnaires in letter Number: 02 / IN / M / 2020 issued by PUPR with a high index level, namely Provision of Health Facilities in the Field of 4.635 standard deviation of 0.593